Timely cholecystectomy: important factors to improve guideline adherence and patient treatment - Sven Hohenstein; Andreas Bollmann; Christian Prinz; Leonard Fehring; Hendrik Brinkmann; Patrick Dirks; Jörg Pölitz (BMJ Open Gastroenterology)
Objective Cholecystectomy is one of the most frequently performed surgeries in Germany and is performed as a treatment of acute cholecystitis (guideline S3 IIIB.8) and after endoscopic retrograde cholangiopancreatography for choledocholithiasis with simultaneous cholecystolithiasis (guideline S3 IIIC.6). This article examines the effects of a guideline update from 2017, which recommends prompt cholecystectomy within 24 hours of admission due to cholecystitis or within 72 hours after bile duct repair. In addition, it aims to identify reasons (eg, financial disincentives) and potential for improvement for non-adherence to the guidelines.Design Methodologically, a retrospective analysis based on routine billing data from 84 Helios Group hospitals from 2016 and 2022, with a total of 45 393 included cases, was applied. The guideline adherence rate is used as the main outcome measure.Results Results show the guideline updates led to a statistically significant increase in the proportion of cholecystectomy performed in a timely manner (guideline S3 IIIB.8: increase from 43% to 49%, p<0.001; guideline S3 IIIC.6: increase from 7% to 20%, p<0.001). Medical, structural and financial reasons for non-adherence could be identified.Conclusion As possible reasons for non-adherence, medical factors such as advanced age, multimorbidity and frailty could be identified. Analyses of structural factors revealed that hospitals in very rural regions are less likely to perform timely cholecystectomies, presumably due to infrastructural and personnel-capacity bottlenecks. A similar picture emerges for maximum-care hospitals, which might be explained by more severe and complex cases on average. Further evaluation indicates that an increase in and better hospital-internal participation of gastroenterologists in remuneration could lead to even greater adherence to the S3 IIIC.6 guideline.